Sistem Pengusir Hama Burung pada Sawah dengan Menggunakan Sensor PIR dan Metode Naive Bayes - Irham Manthiqo Noor; Hurriyatul Fitriyah; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There are various methods in dealing with rice pest attacks. Generally, the method used is less efficient and effective. Research carried out initiated the use of technology, specifically by utilizing the Passive InfraRed Sensor (sensor-PIR) on Arduino-UNO in the eviction of bird pests in the fields. The method using the sensor is able to detect infrared light in the form of heatwaves released by birds. The detection results are then sent to the Arduino UNO next to the servo motor. Utilizing the Naive Bayes method to look for opportunities for success, this study revealed an accuracy percentage of 89.45%. The data computing when the system stops at 1262.5898 milliseconds.